Curriculum and instructions: towards 21st century teaching and learning - Syed Hassan, Sharifah Sariah; Mohin, Mohaida (Pejabat Karang Mengarang (Penerbit UPSI), 2017)
The book entitled Educating The Muslim Adolescents in The 21st Century has been written by Associate Professor Dr Sharifah Sariah Syed Hassan and edited by Assistant Professor Dr Mohaida Mohin. It consists of seven chapters specifically focusing on the current issues related to education. The implications of the related issues include the needs to revise the curriculum in Teacher Education. This book has been designed and written in simple language that target a wide audience which include parents, teachers, lecturers and Higher learning students. It is essential for post graduate students who have the interest in research of Teacher Education and Curriculum as it relates to theory and practice. Teachers in schools can benefit from reading this book as a motivation for self reflection. The source of writing is based on library search, Internet resources and empirical evidence from primary research carried out by the author. Issues related to knowledge and skills in content and pedagogy are highlighted in Chapter 1-Introduction. Finland has been cited to be an example of having good and stable education system where education policies and implementation are free from political influence. The second chapter entitled ‘Parenting in Information and Communication Technology era’ has highlighted the importance to embrace communication technology in the adolescents’ lives. The chapter discusses the importance of partnership between parents and teachers. The roles of teachers and parents are elaborated. Chapter 3- ‘Teaching Through Reflections: Food of thoughts’ bring teachers and educators to evaluate their commitment in educating the students. The importance of values is embedded in effective teaching quality. The histories of world civilizations are discussed briefly as to highlight the contributions of education and values in the society for the nation building. Chapter 4- ‘Promoting Problem Solving Skills In Life: From Problem To Project Based Learning’ brings the readers to conceptualize problem Based learning as essential skills for the success and development of a nation. ICT can be integrated in the curriculum to ensure Problem and Project based learning can take place. Thus, creative and critical thinking can be promoted in ICT learning environment. In Chapter 5- ‘Learning From The Multimedia: New Perspectives Of Learning’ has elaborated on the learning theory involving learning with multimedia. Learning styles and multiple intelligence are discussed to provide explanation on adolescents’ way of learning and thinking. The following chapter ‘Integrating Mobile Technology in Curriculum’ encompasses the Technology Pedagogy Content Knowledge (TPCK) highlighting how mobile technology can be used for teaching and learning. Models of teaching are also discussed when mobile technology in integrated in the classroom. Chapter 7 elaborates the summary of the book. The importance of reforming teachers in school with synergy efforts is analyzed. Japanese Education system is the example cited for the reform of training for teachers. A synergy effort in lesson study has been introduced. The book ends with a summary to conclude the contents discussed.